Monte Carlo calculations of the cellular S-values for α-particle-emitting radionuclides incorporated into the nuclei of cancer cells of the MDA-MB231, MCF7 and PC3 lines. (May 2018) - Rojas-Calderón, E.L.; Ávila, O.; Ferro-Flores, G.
Abstract: S -values (dose per unit of cumulated activity) for alpha particle-emitting radionuclides and monoenergetic alpha sources placed in the nuclei of three cancer cell models (MCF7, MDA-MB231 breast cancer cells and PC3 prostate cancer cells) were obtained by Monte Carlo simulation. The MCNPX code was used to calculate the fraction of energy deposited in the subcellular compartments due to the alpha sources in order to obtain the S -values. A comparison with internationally accepted S -values reported by the MIRD Cellular Committee for alpha sources in three sizes of spherical cells was also performed leading to an agreement within 4% when an alpha extended source uniformly distributed in the nucleus is simulated. This result allowed to apply the Monte Carlo Methodology to evaluate S -values for alpha particles in cancer cells. The calculation of S -values for nucleus, cytoplasm and membrane of cancer cells considering their particular geometry, distribution of the radionuclide source and chemical composition by means of Monte Carlo simulation provides a good approach for dosimetry assessment of alpha emitters inside cancer cells. Results from this work provide information and tools that may help researchers in the selection of appropriate radiopharmaceuticals in alpha-targeted cancer therapy and improve its dosimetry evaluation. Highlights: S -values for alpha sources into the nuclei of three cancer cell geometries were calculated. S -values were obtained for 225 Ac and 211 At radionuclides for the MCF7, MDA-MB231 and PC3 cancer cell models. A comparison with internationally accepted S -values for alpha sources in spherical cells was performed.